Study of physico-chemical and biochemical parameters during rotary drum composting of water hyacinth - D. Sarika; Jiwan Singh; Ravi Prasad; Isha Vishan; V. Sudharsan Varma; Ajay S. Kalamdhad (International Journal of Recycling of Organic Waste in Agriculture)
Background Water hyacinth (Eichhorniacrassipes) is one of the most uncompromising weeds in the whole world. Its adverse effects due to fast growth rate are main physical interference with fishing and navigation. Water hyacinth also causes eutrophication due to the large release of organic nutrients after its degradation, consequentially deterioration of water quality and also adversely affecting aquatic flora and fauna. Therefore, composting is one of the best methods for control and utilization of water hyacinth. Water hyacinth being the plant material is rich in cellulose, hemicellulose, and lignin content which hinders the rate of degradation during composting. The raw materials including water hyacinth along with sawdust and cattle manure in five different proportions trial 1 (10:0:0), trial 2 (8:1:1), trial 3 (7:2:1), trial 4 (6:3:1), and trial 5 (5:4:1) were composted using rotary drum composter. Results Final product of water hyacinth composting was flourishing of nutrients such as nitrogen, phosphorus, sodium, potassium, calcium, and magnesium. The lignin reduction in all the five trials was obtained between 10 and 40 %. The reduction in cellulose was observed ranging from 4 to 55 % in different trials. Similar as cellulose and lignin, hemicellulose was also reduced about 11â46 % in all five trials during the process. Conclusion The maximum reduction inorganic matter, lignin, cellulose and hemicellulose was observed in trial 4; whereas, the nutrient contents (nitrogen, phosphorus, Na, K, Ca, and Mg) were increased significantly during the process. On analyzing the FTIR results, trial 4 showed that aliphatic and polysaccharides have easily degraded and aromatic compounds have increased with composting time in trial 4